Introduction of diagnostic procedures and training programs in the psychological preparation and rehabilitation of winterers - Miroshnichenko, O. A.; Gutsulyak, O. P.; Marchenko, O. V. (Ukrainian Antarctic Journal, 2017)
The article deals with the psychological preparation of Ukrainian winterers for long-term activity under extreme conditions. Objective of the article: to consider the psychological training of Ukrainian winterers for long-term activity in extreme conditions, to substantiate expediency of application of psychological methods of study of readiness for activity, with the help of mathematical apparatus to prove the efficiency of implementation of training programs in the period of rehabilitation the wintering. Methods. The article considers the components of the psychological tools, justifies the feasibility of using the psychological methods of studying readiness for the activity, and also gives a description of how the psychologist conducts psychological examinations, namely: observation, individual conversations, business games, testing with the help of techniques. According to the developed concept of the typology of Ukrainian winterer, the greatest attention is paid to the adaptive capabilities of the individual, which will spend the whole year far from home and usual conditions. Results. Psychological diagnosis is an important part of the selection and training of winterers for extreme conditions in Antarctica. An effective way to reduce the negative impact of life situations to the development of negative psycho-emotional conditions of future winterers is the use of psychological training that is conducted during the training of Ukrainian wintering members for participation in Antarctic expeditions and after returning from the expedition. With the help of a mathematical apparatus, the effectiveness of the implementation of training programs in the period of rehabilitation after the wintering. Conclusions. Professional psycho-physiological selection is one of the most important ways to increase the efficiency of professional activity in the conditions of the Antarctic station. In order to carry out professional psychophysiological selection of future winterers, it is necessary to carry out a clear elaboration of methodological approaches for its implementation. Mandatory requirements for the organization and implementation of professional psycho-physiological selection is standardization of the conditions of conduct, compliance with ethical standards, verification of the effectiveness of psychological tools through the methods of mathematical analysis.